THE CRISIS OF THE MODERN CITY: THE EXAMPLE OF PORTO ALEGRE - Maroneze, Luiz Antonio Gloger (Revista Conhecimento Online: Diversidade e Inclusão Social, 2018)
This article offers an analysis of the effects of the crisis of modernity in the context of the history of Porto Alegre, starting from the understanding that the city has experienced, in a clear way, the modern imagery and, subsequently, the crisis of such ideas. A review of the literature is also presented, looking at important works written by authors who describe this process in Porto Alegre; subsequently, a dialogue with the great minds that address the topic. It is understood that reflecting upon the urban future and urban projects – as well as how these ideas are rearranged – is imperative to contemporary social sciences. Keyword: City. Crisis. Modernity. Violence. RESUMO O artigo propõe analisar os efeitos da crise da modernidade no âmbito da História de Porto Alegre. Parte do entendimento de que a cidade vivenciou de forma clara os imaginários modernos e, posteriormente, a crise destas ideias. Faz-se, na sequência, uma revisão dos autores que analisam esse processo no âmbito da capital para, logo depois, dialogar com os principais pensadores que transitam pela temática. Entende-se aqui que refletir sobre os destinos e projetos urbanos, sobre a forma como essas ideias estão sendo reorganizadas é fundamental as ciências sociais contemporâneas. Palavras-chave: Cidade. Crise. Modernidade. Violência